2021
DOI: 10.1016/j.lanwpc.2021.100281
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of contact tracing by mass testing for successful containment of beta COVID-19 variant (SARS-CoV-2 VOC B.1.351) epidemic in Hong Kong

Abstract: Background: Global dissemination of SARS-CoV-2 Variants of Concern (VOCs) remains a concern. The aim of this study is to describe how mass testing and phylogenetic analysis successfully prevented local transmission of SARS-CoV-2 VOC in a densely populated city with low herd immunity for COVID-19. Methods: In this descriptive study, we conducted contact tracing, quarantine, and mass testing of the potentially exposed contacts with the index case. Epidemiological investigation and phylogeographic analysis were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement ). Fifty-eight new studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 (eTable 2 in the Supplement ) were combined with 77 studies from ou...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement ). Fifty-eight new studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 (eTable 2 in the Supplement ) were combined with 77 studies from ou...…”
Section: Resultsmentioning
confidence: 99%
“…This reflects new variants and changing vaccination coverage. From highest to lowest, the overall household SARs were 42.7% (95% CI, 35.4%-50.4%) for Omicron (7 studies 55 , 61 , 62 , 63 , 64 , 67 , 68 ), 36.4% (95% CI, 33.4%-39.5%) for Alpha (11 studies 18 , 19 , 21 , 23 , 28 , 33 , 44 , 46 , 49 , 50 , 69 ), 29.7% (95% CI, 23.0%-37.3%) for Delta (16 studies 18 , 20 , 24 , 26 , 35 , 37 , 42 , 46 , 50 , 55 , 57 , 61 , 64 , 65 , 66 , 70 ), and 22.5% (95% CI, 18.6%-26.8%) for Beta (3 studies 15 , 18 , 50 ) ( Figure 2 ). High heterogeneity was found among studies for Omicron ( I 2 = 98.2%; P < .001) and Delta ( I 2 = 99.1%; P < .001), moderate for Alpha ( I 2 = 59.6%; P < .001), and low for Beta ( I 2 = 2.6%; P = .79).…”
Section: Resultsmentioning
confidence: 99%
“…Despite some sporadic episodes of SARS-CoV-2 transmission in the designated quarantine hotels between quarantinees,( Wong et al, 2021 , Wong et al, 2021 ) these did not result in a new wave of COVID-19 in our community. Cheng et al, (2021) …”
Section: Introductionmentioning
confidence: 99%
“…At this point of the pandemic, the rapid detection of new cases and the surveillance needed for restoring normal activities are important for monitoring new waves of infection. Cheng and collaborators demonstrated that mass testing for contact tracing combined with phylogenetic analysis prevent new infections in Hong Kong besides its contributions to genomic surveillance of new SARS-CoV-2 variants 13 .…”
Section: Discussionmentioning
confidence: 99%